Controlled-release fertilizer increases growth, chlorophyll content and overall quality of loquat seedlings - Nunes Gomes, Erik; Vieira, Leandro Marcolino; Fagundes, Cíntia de Moraes; Rossa, Überson Boaretto; Tofanelli, Mauro Brasil Dias; Deschamps, Cicero (Comunicata Scientiae, 2020)
Eriobotrya japonica (Thunb.) Lindl. (Rosaceae), commonly known as the loquat tree, is widely cultivated due to production of edible fruits, which can be consumed fresh or processed into different food products. Enhancement of loquat seedlings quality is an important issue for more efficient propagation protocols, including rootstock production. The objective with the present study was to assess the effects of increasing doses of controlled-release fertilizer on loquat seedlings growth, quality and chlorophyll content. Seeds were sowed in containers filled with commercial substrate previously treated with different doses of controlled-release fertilizer (N, P, K, Mg, S and micronutrients): 0.0 (control), 2.5, 5.0, 7.5 and 10.0 kg per cubic meter of substrate (kg m-³). Seedlings were evaluated 182 days after sowing and the data were submitted to polynomial regression analyses. Increasing doses of the fertilizer promoted increasing linear behavior on seedlings height, root collar diameter, leaf area, roots and shoots dry mass and Dickson quality index. Chlorophylls a, b and total chlorophylls increased up to the dose of 7.5 kg m-³, followed by a decrease at the dose of 10 kg m-³. The dose of 10 kg m-³ promoted the highest values of Dickson quality index and growing variables on loquat seedlings.